National reckonings : the Last Judgment and literature in Milton's England - Hackenbracht, Ryan (Cornell University Press, 2019)
"Shows how Milton, Hobbes, and other seventeenth-century English writers used expectation of the world's end to invent new and radical ideas of the nation"--